Railway Mergers and Railway Alliances: Competition Issues and Lessons for Other Network Industries - Russell Pittman (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2009)
Freight railway enterprises in both Europe and North America are in the process of significant restructuring, with EC policy changes dictating new ownership, organization, and cooperation arrangements in Europe and a series of major mergers having already led to highly concentrated regional markets in the U.S. and Canada. Mergers, alliances, and organizational changes may raise important and complex issues regarding the level of competition facing goods shippers, with differing implications depending on the differing institutional contexts. This paper examines the competitive consequences of these developments in Europe and North America and suggests some lessons for other network industries.
Keywords: 330; railway; competition; mergers; alliances